Temperature‐sensitive sodium beta‐glycerophosphate/chitosan hydrogel loaded with all‐trans retinoic acid regulates Pin1 to inhibit the formation of spinal cord injury‐induced rat glial scar - Rongmou Zhang; Ting Tang; Huafeng Zhuang; Peiwen Wang; Haiming Yu; Hao Xu; Xuedong Yao (Bioengineering & Translational Medicine)
Abstract Glial scar formation is a major obstacle to nerve regeneration following spinal cord injury (SCI). Pin1 and the PI3K/AKT/CDK2 signaling pathway play crucial roles in neuronal regulation, but research on their involvement in glial scarring remains limited. In this study, we have for the first time observed that Pin1, PI3K, AKT, and CDK2 are upregulated and interact with each other following SCI. Further experiments revealed that Pin1 contributes to the development of glial scars by promoting astrocyte proliferation, inhibiting apoptosis, and activating the PI3K/AKT/CDK2 pathway. Additionally, all‐trans retinoic acid (ATRA), a specific chemical inhibitor of Pin1, effectively suppresses Pin1 expression. However, its clinical application is limited by its short half‐life and susceptibility to inactivation. To address these issues, we have developed a thermosensitive sodium beta‐glycerophosphate (β‐GP)/chitosan (CS) hydrogel loaded with ATRA (β‐GP/CS@ATRA). This hydrogel exhibits favorable morphology and biocompatibility. Compared to free ATRA, the β‐GP/CS@ATRA hydrogel significantly enhances functional motor recovery after SCI and protects spinal cord tissue, thereby inhibiting glial scar formation. Mechanistically, ATRA administration blocks the development of glial scars and the activation of the PI3K/AKT/CDK2 pathway by inhibiting Pin1 expression. This study suggests that combining ATRA with a hydrogel to target Pin1 expression may be a promising strategy for treating glial scar formation following SCI.